Rumah Sehat pada Masyarakat Pesisir Kabupaten Minahasa Utara - Oksfriani Jufri Sumampouw; Arlin Debora Tongkotou (Universitas Sam Ratulangi, 2024)
Background: One of the environmental health problems in Indonesia is a healthy house, especially in the components of the house, sanitation facilities, and the behavior of residents in a state that does not meet health requirements. An unhealthy house can be at risk of diseases in the residents of the house such as tuberculosis, diarrhea, and others. This study aims to find out the description of healthy houses from the community in the coastal communities of North Minahasa Regency. Methods: This is a descriptive research. A total of 50 houses were sampled in this study. Sample selection uses accidental sampling technique. The research was conducted in the Kema Health Center Working Area in June-August 2023. Data was obtained through a healthy house assessment questionnaire from the Indonesian Ministry of Health based on home components, sanitation facilities, and resident behavior. Data analysis was carried out univariately. Results: The results showed that based on the components of a healthy house, the majority of respondents found the state of the kitchen smoke pit which has kitchen ventilation <10% of the floor area. Based on the sanitation component, it was shown that the majority of respondents who had clean water facilities were included in the category of not meeting health requirements with a total of 19 respondents, the condition of latrines that were included in the category of not meeting the requirements amounted to 4 respondents and those who did not have latrines amounted to 2 respondents. Furthermore, if studied based on the components of health behavior, it was found that most respondents threw garbage and feces of children carelessly, such as into rivers or gardens. Conclusion: It can be concluded that around 70% of households from people who have toddlers in the Working Area of the Kema Health Center, North Minahasa Regency have not met the health requirements according to the indicators of the components of home, sanitation, and health behavior.